Numerical Solutions Of Nonlinear Boundary Value Pantograph Type Delay_x000D_ Differential Equations - YILMAZ, BÜLENT (My University, 2020)
In this paper we compared the Daftardar-Jafari Method (DJM) with Adomian Decomposition Method (ADM) and DifferentialTransformation Method (DTM) in solving nonlinear boundary value delay differential equations of pantograph type. All these3 methods provide series solutions to the problems. We analysed the first n-term approximate solutions of these 3 methodswith 2 numerical examples to see if DJM is as good as ADM and DTM in solving nonlinear boundary value delay differentialequations and we found DJM a reliable method in solving this kind of problems.

Bu çalışmada doğrusal olmayan sınır değerli pantograf tip gecikmeli diferansiyel denklemlerin çözümünde Daftardar-Jafari_x000D_ Metodunu (DJM), Adomian Ayrıştırma Metodu (ADM) ve Diferansiyel Transformasyon Metoduyla (DTM) karşılaştırdık. Bu_x000D_ 3 metot ta seri formunda çözümler oluştumaktadır. Bu 3 metodun ilk n-terimli yaklaşık çözümlerini 2 nümerik örnekle analiz_x000D_ ederek DJM nin sınır değerli gecikmeli diferansiyel denklemlerin çözümünde ADM ve DTM kadar iyi olup olmadığını_x000D_ araştırdık ve sonuç olarak DJM nin bu tip problemlerde güvenilir bir metot olduğunu gördük.
Doğrusal Olmayan Sınır Değerli Pantograf Tip Gecikmeli Diferansiyel Denklemlerin Nümerik Çözümleri